ANALYSIS OF ECONOMIC INDICATORS FOR BOSNIA AND HERZEGOVINA IN THE PERIOD 2010-2016 YEAR - Šušić, Milan (Journal of process management and new technologies, 2018)
The paper analyzes the macroeconomic data presentation system in the period from 2010 to 2016, which provides an insight into the overall economy (one piece of data). Data are central to the statistical system and are an indispensable basis for conducting economic policy and decision-making at all levels, since they allow measuring the level of economic development, the rate of economic growth, changes in production, consumption, savings, investments, exports and imports. In the system of national accounts there are value categories that are called aggregates and which have wide application in everyday practice. Aggregates are important macroeconomic indicators that measure the results of the economies of a country and are used for macroeconomic analysis. The basic and most important macroeconomic aggregate in the system of national accounts is gross domestic product (GDP). The paper analyzes GDP, real GDP growth rate, industrial production, labor market, unemployment and comparison with EU countries, demographic trends in B & H and Republika Srpska. By using  of mathematical-statistical methods it was established legality of production trends in the observed period. Based on the analysis of the mentioned parameters,they were established  conclusions are drawn that point to the activities that they to be taken for the faster economic development of Bosnia and Herzegovina.